2010
DOI: 10.1080/02786826.2010.504245
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Primary and Secondary Components of PM2.5Composition for an Urban Atmosphere

Abstract: Total 360 samples (of 8 h each) of PM 2.5 were collected from six sampling sites for summer and winter seasons in Kanpur city, India. The collected PM 2.5 mass was subjected to chemical speciation for: (1) ionic species (NH 4 : 13%; NO -3 : 11%). The secondary organic component was 12% in summer and 18% in winter. In conclusion, secondary aerosol formation (inorganic and organic) accounted for significant mass of PM 2.5 (about 50%) and any particulate control strategy should also include control of primary pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…The contributions of SOA to PM 2.5 were 5-8%, 4-19%, 18-21% and 13-17% during the spring, summer, autumn and winter, respectively. The results showed the same seasonal trends as reported by Behera and Sharma (2010) for Kanpur, India, who concluded that the SIA and SOA of PM 2.5 were approximately 34% and 12% in the summer and 32% and 18% in the winter, respectively.…”
Section: Secondary Componentssupporting
confidence: 76%
See 1 more Smart Citation
“…The contributions of SOA to PM 2.5 were 5-8%, 4-19%, 18-21% and 13-17% during the spring, summer, autumn and winter, respectively. The results showed the same seasonal trends as reported by Behera and Sharma (2010) for Kanpur, India, who concluded that the SIA and SOA of PM 2.5 were approximately 34% and 12% in the summer and 32% and 18% in the winter, respectively.…”
Section: Secondary Componentssupporting
confidence: 76%
“…Therefore, secondary fractions are important for controlling PM 2.5 pollution. Previous studies (Cabada et al, 2002;Tao et al, 2009;Behera and Sharma, 2010) have shown that secondary organic aerosols (SOA) are an important component of PM 2.5 . The contributions of SOA to the total organic carbon (OC) concentration vary from nearly zero during the winter to 50% during the summer in Pittsburgh, Pennsylvania.…”
Section: Introductionmentioning
confidence: 99%
“…Kanpur city, one of the most polluted cities in the World, has a variety of industries like cotton, wool, jute and tanneries. The sources of air pollution are mainly categorized into industrial, commercial, transport, domestic, institutional and fugitive (Behera and Sharma, 2010;Gupta and Mandariya, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These are inherent problems that require addressing, however they were will require significant effort to improve. In the present study, anthropogenic emissions are divvied up evenly into days, and allocated during typical emitting hours per sector.More detailed temporal emissions distributions have been quantified, mostly in Delhi [Guttikunda and Calori, 2013;Pant et al, 2015], and season specific emissions have been measured across urban areas using tracers in source apportionment studies [Chowdhury et al, 2007;Behera and Sharma, 2010;Ghosh et al, 2014]. Currently, monthly variations in ambient air quality are the result of meteorological impacts, where greatest pollution was evident in the winter, when PBL heights are shallow, and lowest during the monsoon season due to pollution "rain out."…”
Section: Discussionmentioning
confidence: 99%